Trade and development of small island economies with particular reference to the South Pacific - Kakazu, Hiroshi (UNCRD NagoyaJP, 1986)
Reviews literature on development problems pertinent to small island economies. Describes general characteristics and problems of small island economies including their narrow resource bases, small domestic markets, chronic trade deficits, diseconomies of scale, rapid population growth, dependence on government as a major source of income and employment, and distances from amjor markets. Examines the role of trade in amall island economies.